Management of New Student Admissions at SMPN 215, West Jakarta - Maulida, Khalifah; Dewi Puspitasari; Meldea Henmadeni; M. Ibnu Muzakir; Baiq Vina Handayani (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2026)
This study aims to analyze and describe the process of managing new student admissions at SMPN 215 West Jakarta. The management of new student admissions is an essential part of efforts to ensure the achievement of the school’s vision and mission, as well as to meet the educational needs of competent students. This study employs a qualitative approach with data collection techniques through interviews, observations, and documentation studies. The research results show that the management of new student admissions at SMPN 215 West Jakarta involves several stages, starting from socialization, registration, selection, to the announcement of selection results. This process involves various parties, including the admission committee, teachers, and parents of the students. Furthermore, the implementation of a technology-based information system facilitates the registration and selection processes. However, challenges related to the limitations of facilities and infrastructure still need attention. Overall, the management of new student admissions at SMPN 215 West Jakarta has been carried out well, although there are some aspects that require improvement to enhance the quality and efficiency of its implementation in the future.